Transforming Healthcare through Comprehensive Interdisciplinary Collaboration: Integrating Public Health, Dentistry, Nutrition, Nursing, Laboratory, Anesthesia, and Radiology for Holistic Patient Care - Mukhtar Abdullah Alhadab,; Sharaf Dhia Alzaidani,; Ali Abdulrazzaq Sulais,; Tahani Marzooq Saad Alsafar,; Zainb Hussain Alfarhan,; Areej Mohammed Alghannam,; Waleed Yahya Abdullah Shami Mls,; Amal Yahya M. Almadah Mlt,; Mohammed Hassan Mohammed Asiri,; Ahmed Ali Ahmed Alshehri,; Yasser Saeed Almalki,; Bader Hamad Saad Alabdulwahab, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The transformation of healthcare requires an integrated, patient-centered approach that considers all facets of health and well-being. Interdisciplinary collaboration between diverse healthcare disciplines—including public health, dentistry, nutrition, nursing, laboratory science, anesthesia, and radiology—offers an opportunity to enhance the quality, efficiency, and comprehensiveness of care. This paper explores the benefits and challenges of such collaboration, focusing on how the integration of these disciplines can lead to more holistic, effective care. By examining each discipline’s contributions and proposing strategies to overcome barriers, the manuscript advocates for a comprehensive approach to healthcare that improves patient outcomes and enhances system efficiency.